2021
DOI: 10.1155/2021/9961628
|View full text |Cite
|
Sign up to set email alerts
|

Ferritinophagy‐Mediated Ferroptosis Involved in Paraquat‐Induced Neurotoxicity of Dopaminergic Neurons: Implication for Neurotoxicity in PD

Abstract: Parkinson’s disease (PD) is a progressive nervous system disorder. Until now, the molecular mechanism of its occurrence is not fully understood. Paraquat (PQ) was identified as a neurotoxicant and is linked to increased PD risk and PD-like neuropathology. Ferroptosis is recognized as a new form of regulated cell death. Here, we revealed a new underlying mechanism by which ferritinophagy-mediated ferroptosis is involved in PD induced by PQ. The effect of PQ on movement injury in mice was investigated by the bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 54 publications
(62 reference statements)
0
31
0
Order By: Relevance
“…CEP served an effective protective role by reducing the accumulation of MDA and 4-HNE and recovering the declined GSH content (Figures 4(a) , 4(b) , and 4(d) ). GPx4 and xCT play an important role in resisting lipid peroxidation [ 29 , 30 ]. However, CEP treatment was showed no effective recovery of GPx4 activity in SAH mice after three consecutive days of CEP treatment ( Figure 4(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…CEP served an effective protective role by reducing the accumulation of MDA and 4-HNE and recovering the declined GSH content (Figures 4(a) , 4(b) , and 4(d) ). GPx4 and xCT play an important role in resisting lipid peroxidation [ 29 , 30 ]. However, CEP treatment was showed no effective recovery of GPx4 activity in SAH mice after three consecutive days of CEP treatment ( Figure 4(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…Washing with PBS, the fluorescence intensity (Ex/Em = 490 nm/515 nm) was quantified by a multifunctional microplate reader microplate. The intracellular lipid ROS levels were detected by BODIPY 581/591 C11 probe (D3861, Thermo Fisher Scientific) [ 29 ]. Cells were incubated with a 2 μM probe for 37°C for 15 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on aging-related diseases have indicated that ferroptosis contributes in the pathogenesis of Alzheimer's disease (230-232), Parkinson's disease (233,234), Huntington's disease (235), Depression (236-238), Osteoarthritis (239), Myocardial ischemia and reperfusion (MI/R) (240)(241)(242), Atherosclerosis (243, 244), and Diabetes (245,246). Notably, quercetin shows iron-chelating activity and effectively decrease iron deposition in the hearts, kidneys and liver of iron-dextran-overloaded mice (247), and protects bone marrow-derived mesenchymal stem cells from erastin-induced ferroptosis through antioxidant pathway (248).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%